2013
DOI: 10.1080/17441692.2013.861859
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of Peru's HIV grant proposals to the Global Fund

Abstract: 2 Peru has applied to six of the Global Fund to Fight AIDS, Tuberculosis and Malaria (the Global Fund) rounds for funding, achieving success on four occasions. The process of proposal development has, however, been criticised, especially concerning the use of evidence, relevance/consistency, and performance indicators.We aimed to analyse the Peruvian Global Fund proposals according to those dimensions, providing feedback to improve future local efforts and inform global discussions around Global Fund procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, they have privileged technological fixes to public health issues, denying the embeddedness of health systems within broader social, economic and political realities. This trend has been reinforced by public health research itself, which has been dominated by quantitative, deductive studies to the detriment of qualitative, inductive research that is more amenable to in-depth understanding of the multifaceted dimension of health issues (Cáceres, Amaya, Sandoval, & Valverde, 2013;Gideon & Porter, 2015). The instrumental role of the BMGF in promoting an overly technological and managerial approach over the 'messy and complicated politics' of public health (Birn, 2014, p. 12) has been particularly emphasised (Birn & Lexchin, 2011;McGoey, 2014;Moran, 2011;Storeng, 2014).…”
Section: Success or Failure? The Doubtful Efficiency / Effectiveness mentioning
confidence: 99%
“…In addition, they have privileged technological fixes to public health issues, denying the embeddedness of health systems within broader social, economic and political realities. This trend has been reinforced by public health research itself, which has been dominated by quantitative, deductive studies to the detriment of qualitative, inductive research that is more amenable to in-depth understanding of the multifaceted dimension of health issues (Cáceres, Amaya, Sandoval, & Valverde, 2013;Gideon & Porter, 2015). The instrumental role of the BMGF in promoting an overly technological and managerial approach over the 'messy and complicated politics' of public health (Birn, 2014, p. 12) has been particularly emphasised (Birn & Lexchin, 2011;McGoey, 2014;Moran, 2011;Storeng, 2014).…”
Section: Success or Failure? The Doubtful Efficiency / Effectiveness mentioning
confidence: 99%
“…Other concerns can also arise. For example, Cáceres et al (2013) found that broader knowledge around HIV/AIDS prevention can become lost in practice where the medical components of models are prioritized over and above other more participative approaches involving a wider range of stakeholders.…”
Section: 'Perverse Outcomes' On the Ground: Ngos Hiv/aids And Maternmentioning
confidence: 99%
“…Indeed, this reinforces the findings in other studies, for example, in relation to work around HIV/AIDS in the context of the Global Fund. Cáceres et al (2013) found that broader knowledge around HIV/ AIDS prevention can become lost in practice where the medical components of models are prioritised over and above other more participative approaches involving a wider range of stakeholders.…”
Section: Negotiating Ngo Relationships With Private Sector Partners At the Local Levelmentioning
confidence: 99%